(untitled) (Fiep Bulletin - online, 2014)
The «Polisportiva Giovanni Masi» (PGM) has been analyzed for 3 years by our research group since 2010. The club, which boasts more than 7000 members, is located in Casalecchio di Reno, a municipality of 38000 inhabitants near Bologna. The research, based on the case-study approach (Yin, 2009) has been carried out with a special focus on the quality of the services, the level of satisfaction of the members, the organizational processes, questionnaires with members (n=1100), in-depth interviews (n=11), focus groups (n=9), life histories (n=4) and observations have been interpolated. Results show that PGM is recognized as a high quality organization. The main factors of the high degree of the members’ satisfaction for the provided services (very good=12,7%, good=77,6% of the respondent) are the relationships with the sports educators/coaches/instructors - 50% of them holding a Physical Education or Sport Sciences degree- (very satisfied=58,9%, satisfied=27,8%) and the assessment of their professional competences (very good=43,4%, good=40,7%). Data collected, which highlight as the success of the organization is, above all, linked to the quality of the didactics, are deeply rooted in the history of PGM. In fact, it has been within the first associations to: propose psychomotricity classes in 1975, as well as baby swimming; invest in high quality training develop and adopt an educational internal code.PGM witnessed a process of professionalization as well as a trend that made communication and decisional procedures more complex. On the light of that, the monitoring carried out during the second and third years of the study, shows that PGM reacted with the rationalization of the internal structure and organizational procedures and with the involvement of a more professionalized workforce.